The 360° TitaniUM Core Strength Exercise® Improve Balance in Teenager - Boon Hooi, Lim; Eng Wah, Teo; Van Bac, Nguyen; Thanh Anh Khoa, Pham; Danh Na, Phan (International Journal of Psychosocial Rehabilitation, 2020)
The core is described as an anatomical box consisting of 29 pairs of muscles forming a front (abdominals), back (paraspinals and gluteals), top and bottom (pelvic floor and hip girdle). It represents the connection between lower and upper limbs and should be considered as a functional unit in which different muscles interact, even if not located in the thoraco-lumbar region (such as shoulders and pelvic muscles). Exercises involving the full body linkage such as core strength training have been advocated to enhance the capacity of transmitting force through the body linkage. Balance is ability to maintain a stable posture with body mass centre in the domain of base of support while counteracting external or internal conflicts. Several potential mechanisms exist to explain ability to improve balance, most of which involve the improved functioning of the nervous system or strengthening of the core. The 360° TitaniUM Core Strength Exercise® is a new sequence of exercise to strengthen the core region muscles, it consisted of twelve isometric exercises and the participants carried out the exercises in sequence with each exercise session consisted of 10-20 seconds/exercise progressively, 3 sets every session with the rest period of one minute between sets. The primary aim of this study was to explore whether 12-week of 360° TitaniUM Core Strength Exercise® could elicit significant improvement of balance stability in teenager. 40 teenagers, 20 males and 20 females age 14 to 16 years old were recruited for this study. Results revealed that 12 weeks 360° TitaniUM Core Strength Exercise® induced significant improvements of balance stability in teenager between pre-test and post-test [t (39) =-8.29, p<0.001]. From the results of this study, we can conclude that the 360° TitaniUM Core Strength Exercise® is suitable and effective training method to improve the balance stability in teenager.